Investment Commitments Reach a New Peak in South Asia While the Number of New Projects Declines - Izaguirre, Ada Karina (World Bank, Washington, DC, 2012)
Private activity in infrastructure in South Asia showed mixed results in 2008, according to just-released data from the private participation in infrastructure project database. Investment commitments to infrastructure projects with private participation reached a new peak thanks to additional investment in existing telecommunications operators and new energy and transport projects that reached financial or contractual closure in the first half of the year. But investment in new projects slowed in the second half of the year with the full onset of the financial crisis. This slowdown led to a decline in the number of projects for the entire year. The region accounted for 22 percent of the year's total investment commitments in developing countries. In 2008, 36 infrastructure projects with private participation reached financial or contractual closure in three South Asian countries (Bangladesh, India, and Pakistan). These projects involve investment commitments of US$17.9 billion. Infrastructure projects implemented in previous years had additional commitments of US$15.4 billion, bringing total investment in 2008 to US$33.4 billion. That represented an increase of 12 percent from the level reported in 2007 and a new peak for the region. Both new and existing projects accounted for the increase. Investment in new projects increased by 8 percent from the level in 2007, while investment in existing projects rose by 18 percent.